Assessing the coastal sensitivity to oil spills from the perspective of ecosystem services: A case study for Canada's pacific coast - Feng, Qi; An, Chunjiang; Chen, Zhi; Owens, Edward; Niu, Haibo; Wang, Zheng (Journal of environmental management, 2021)
Coastal environment is one of the most important ecological and socioeconomic areas. However, increasing energy demand and economic development lead to a continuous gas and oil exploration, production, and traffics, which notably raise the risk of oil spill accidents in coastal areas. Sensitivity assessment aiming to determine the coastal features that would be severely impaired by spill incidents is a crucial part of the response planning. In this study, an innovative framework for coastal sensitivity mapping that incorporated ecosystem service (ES) valuation and multidimensional assessment was proposed. Sensitivity was computed by valuing physical, biological, and social-economical indicators from ES perspective and separating each indicator into specific coastal domains. For different ES typologies, provisioning services contributed most to the overall ES value followed by culture services, supporting services, and regulating services. For ES value in different coastal domains, the highest value was recorded in the water column followed by water surface, shoreline, and seabed. However, the shoreline ranked highest regarding the ES value per ha. Sensitivity assessment revealed that sensitive areas differed in different domains, both in distribution and extent. Compared with the scoring method, the ES valuation method showed more coincidence with Ecologically and Biologically Significant Areas (EBSA), representing a more precise and practical approach for sensitivity assessment. A three-dimensional (3D) oil spill model was also applied to generate maps of oil contamination probability in shoreline, water surface, and water column. The obtained results highlighted the significance of incorporating different coastal domains into oil spill responses, and the urgent demand to broaden and deepen our understanding of ecological processes across the vertical coastal zones. [Display omitted] •An innovative framework for coastal sensitivity mapping was proposed.•ES valuation and multidimensional assessment were incorporated for analysis.•A case study was conducted to assess the sensitivity of Canada's Pacific coast.•ES valuation method is more precise and practical compared with the scoring method.•Sensitive areas differed in different domains, both in distribution and extent.